The effect of safety leadership, safety culture, and safety behavior on safety performance after a company merger: a case study - Cintya Dyah Atikasari; Adithya Sudiarno; Edi Priyanto (Jurnal Sistem dan Manajemen Industri, 2022)
After the merger of PT Pelindo, PT Pelindo Terminal Petikemas became one of the sub-holding companies in containers. In maintaining consistency with the implementation of Occupational Health and Safety (OHS) after the merger, PT Pelindo Terminal Petikemas needs to understand the importance of safety leadership, safety culture, safety behavior, and safety performance in the OHS program's success. The study aimed to determine the effect of safety leadership on safety culture and safety performance, the effect of safety culture and safety behavior on safety performance, and safety behavior to act as a mediation between safety leadership and safety performance, and safety culture on safety performance at PT Pelindo Terminal Petikemas. The samples of 130 employees are then analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The results showed that safety leadership has a significant effect on safety culture and safety performance. Safety culture and safety behavior have a significant effect on safety performance. Safety behavior can mediate between safety culture and performance, while safety behavior cannot act as a mediation between safety leadership and performance. This research implies that PT Pelindo Terminal Petikemas's management can select several strong and trustworthy employees from each terminal who merge to lead initiatives regarding company safety and communicate with the central command.